Scientific, scientific-methodological and organizational report “The Institute of theoretical mathematics and scientific computing (ITMSC) L.N.Gumilyov Eurasian National University in 2019 year (Part I)” - Temirgaliyev, Н. (Bulletin of L.N. Gumilyov Eurasian National University. Mathematics, computer science, mechanics series, 2020)
As the name implies, the Report is conducted in three areas: science, methodology of basic mathematical training, and organization and management of Education and Science. Probably, on the issue of Education problems and what should be done here, it is impossible to say better than the materials of the Collection "Education that we can lose" on the example of Russia and the United States. At the same time, we see something else - 20 years have passed since then, and based on the current state of school education, we can draw a principled conclusion that highly reasoned correct words themselves do not have decisive consequences. In two examples, and it is repeatedly checked in detail on the methodological development of "multiplication table" and the devastating "Rule of addition of fractions" are shown requires a decomposition into simple denominators (back then, the RSA System (Rivest, Shamir, Adelman; 1978) built on the practical difficulties of such decomposition): the highest quality declarations cannot stimulate what is necessary and cannot stop what is unnecessary. If it is about science, then again, the question arises "how to evaluate science both internally and externally in order to have an effective Science". Here a comprehensive answer is given in the form of a mandatory annual filling out of the "Scientific and methodological passport of an employee of research Institutes and teaching staff of universities", on the basis of which the state will plan which domestic promising research and at what level to support through appropriate funding. It is this "Scientific and methodological passport" that allows us to introduce a new type of scientific event both within the country and internationally to represent the host country as a carrier of advanced science in some areas - this is through "Activation reports". Of course, with the paradigm "Science is either there or it is not", the issue of evaluating the quality of scientific research, which is not fully formalized, here, of course, we must listen to those who formed and took place in the highest scientific atmosphere. So, in our understanding, productive research worker and witness to the flourishing period of mathematics of Moscow University is V. N. Latyshev (here it is necessary not to lose sight of the fact that while statistics MSU was this -from 10 students one candidate out of 10 candidates one doctor - this was super requirements) "I remember the basement of an article by M. V. Keldysh (the longtime President of the USSR, "Head theoretician of cosmonautics"), this is a great article in the newspaper "Pravda", which says "a Huge number of mathematicians is remarkable, for which there are no results." But this does not mean that they are bad. If a mathematician has at least one result, it is a very good mathematician. More than one almost never happens, if two, it is absolutely wonderful. Such finds come only once in a lifetime." There are some Sciences that you can enter immediately, perhaps after a little training. But mathematics is a very special science, for its implementation, it is necessary to go through all the stages of its origin and development in order to understand the higher problems in it and, moreover, to participate in their development. You have to go all the way through high school from first to last grade. Here we highlight the state of "Understanding mathematics", which may again not be formalized, and which undoubtedly exists in reality. All this is very relevant: again, the Collection "Education that we can lose" shows that this part of the introduction to mathematics remains out of everyone’s attention. Here, the topic of "Understanding mathematics" is being developed, and, as we were surprised to find out, this is the way to the profession of the legendary Gottfried hardy. There is another personal aspect of the relationship between studying science and creating a textbook on this science, which is also discussed. Finishing the excursus on the content of the Report, we repeat once again that the internal interests of Kazakhstan are being pursued with the presentation of scienti